DESIGN OF LINEMANTOOLS WITH VOLTAGE DETECTOR - Ahmad Ridowi; Dody Wahjudi; Tri Watiningsih (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
PLN officers often experience obstacles in placing equipment and materials when working on poles. Toovercome this problem, officers use ropes, carabiners, and safety belts or safety belts there are specialplaces to put the equipment, but the existing equipment has many shortcomings, namely difficulty in placingand retrieving equipment and constrained in movement or maneuvering. This can cause the equipment ormaterial to fall, thus endangering the staff underneath and causing loss due to damage to the tool or theenvironment.In order to achieve K2 (Electricity Safety) and K3 (Occupational Safety and Health) and maintain company image, in overcoming this problem, a tool called "Lineman Aids with Voltage Detector" is a tool to assist in carrying and placing equipment or materials when working on electric poles. This toolis designed using a magnetic system that is strong, safe and practical so that the lineman or officer easilyputs and picks up items when maneuvering and working on poles. This tool is also equipped with a voltagedetection alarm to maintain a safe distance from the voltage source when doing maintenance work withoutoutages.Key Word : Lineman, Safety Belt, K2 and K3, ProtectionABSTRAKPetugas PLN sering mengalami kendala dalam menaruh peralatan maupun materialsaat bekerja diatastiang.Untuk mengatasi masalah tersebut, petugas menggunakan tali, carabiner, dan sabuk pengaman atausafety belt terdapat tempat khusus untuk menaruh peralatan, tetapi alat yang sudah ada mempunyai banyakkekurangan, yaitu kesulitan dalam menaruh dan mengambil peralatan serta terkendala dalam pergerakanatau manufer. Hal tersebut dapat menyebabkan peralatan atau material terjatuh, sehingga membahayakanpetugas dibawahnya serta menyebabkan kerugian akibat kerusakan alat maupun lingkungan. Gunatercapainya K2 (Keselamatan Ketenagalistrikan) dan K3 (Keselamatan dan Kesehatan Kerja) serta menjagacitra perusahaan maka dalam mengatasi masalah tersebut, dibuatlah alat yang diberi nama â€œAlat BantuLineman dengan Voltage Detectorâ€, yaitu alat untuk membantu dalam membawa dan menaruh peralatanatau materialÂ  pada saat bekerja di atas tiang listrik. Alat ini didesain menggunakan sistem magnet yangkuat ,aman dan praktis sehingga lineman atau petugas mudah menaruh dan mengambil barang pada saatmanuver dan bekerja diatas tiang. Alat ini juga dilengkapi dengan alarm pendeteksi tegangan untukmenjaga jarak aman dari sumber tegangan pada saat melakukan pekerjaan pemeliharaan tanpa padam.Kata Kunci : Lineman, Safety Belt, K2 dan K3, Proteksi Â